SOLVENT-FREE SYNTHESIS OF AMIDE: A NOVEL TECHNIQUE OF GREEN CHEMISTRY - GOHIL, CHIRAGKUMAR J; N NOOLVI, MALLESHAPPA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Amide is one of the most important functional group presents in the chemicals, pharmaceuticals, and foods. Conventionally, it has been synthesized from the carboxylic acid and amines. This conventional reaction is lengthy and involves hazardous chemicals and solvents. Hence, it poses waste management, solvent removal, and environmental issues to the industries. To overcome this limitation, we have reported the green chemistry-based method for the synthesis of amide from carboxylic acid and urea. Methods: In this reaction, we have used boric acid as a catalyst, it is a simple and readily available compound. It is simple, efficient, and solvent-free procedure which involves the trituration of the reactant mixture and subsequent, direct heating of the triturated mixture. Results: The rate of reaction is very high and can synthesize the amide quickly. Conclusion: Various amides were prepared in good yield by this technique.